Effect of Humic Acid Applications on Physiological and Biochemical Properties of Soybean (Glycine max L.) Grown under Salt Stress Conditions - Noor Maiwan BAHJAT; Murat TUNCTURK; Ruveyde TUNCTURK (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
In the study, humic acid was applied to soybean (Glycine max L.), which has high economic value and importance, to determine the tolerance level of the plant against salt stress, and physical and chemical changes in the plant were observed. The study was carried out in the climate room of Van Yuzuncu Yil University Faculty of Agriculture, Department of Field Crops in 2019. In the research, İlksoy soybean variety was used. The experiment was carried out in 4 factorial orders according to the factorial experiment was designed based on Completely Randomized Design. In the research, four different Humic acid doses (0, 500, 1000 and 2000 ppm) and 3 different NaCl salt doses (0, 125 and 250 mM) were used. In the study, root length, stem length, root fresh weight, stem fresh weight, root dry weight, stem dry weight, leaf area, chlorophyll content, ion leakage in leaf tissues, lipid peroxidation level (MDA), relative water content and membrane resistance index in leaf tissues were determined. Properties such as index were also examined. As a result of the study, the longest root was 38 cm for the control plots that salt and humic acid didn’t apply to the plants. The highest root fresh weight was 2.08 g and the stem fresh weight was 1.87 g of the plots where 500 ppm humic acid dose applied. In addition, the plants with the highest chlorophyll ratio was 51.05 under 250 mM salt applied without humic acid application.